Mechanically Harvesting Hard Cider Apples Is More Economically Favorable than Hand Harvesting, Regardless of Farm Scale - Karl, Adam; Knickerbocker, Whitney; Peck, Gregory (HortTechnology (Alexandria, Va.), 2022)
Harvesting labor is the largest annual variable operating expense for apple ( Malus × domestica ) orchard enterprises and is subject to escalating costs and shortages. In Europe, much of the cider apple harvesting is done with machinery, greatly reducing production costs. However, despite a rapid increase in hard cider production in North America over the past 15 years, mechanical cider apple harvesting has not been widely implemented. In this study, we compared mechanical with hand harvesting costs for model 5-, 15-, and 60-acre cider apple orchards located in New York using a partial budget model. Scale-appropriate harvesters were identified for use at each farm scale. Sensitivity analyses were used to test the cost differential for using each piece of machinery on varying orchard sizes and to model changes in labor costs. Across all orchard scales, we found that mechanically harvesting cider apples was more profitable than hand harvesting, with larger operations breaking even sooner and realizing greater returns than operations using hand harvesting. Mechanical harvesting costs broke even with hand harvesting in years 16, 7, and 5 and by year 30 reduced cumulative harvesting costs by 23%, 52%, and 53% in our 5-, 15-, and 60-acre model orchards, respectively. Increasing the orchard size resulted in greater returns from mechanical harvesting. Using the machinery in the 15-acre orchard scenario on a 30-acre farm resulted in costs breaking even with hand harvesting in year 3; by year 30, the cumulative costs resulted in 66% lower harvesting costs than hand labor. Mechanical harvesting remained profitable when labor wages were decreased and became more profitable in scenarios with increasing wages. For example, in the 60-acre orchard, mechanical harvesting cost 41% less than hand harvesting with a 2% annual compounding decrease in labor wages; with 2% annual compounding increase in labor wages, the mechanical harvesting cost was 63% less than hand harvesting. In addition to the cost savings, mechanical harvesting allows for harvesting cider apples with fewer logistical challenges, such as contracting, housing, and transporting migrant labor.